Class Consciousness, Service Work: youth and class in Nanjing vocational secondary schools. - Woronov, T.E. (Journal of Contemporary China, 2012)
This essay discusses an interesting paradox forming in urban China today. Using a Weberian framework, it argues that recent changes in state policy, educational structures, and forms of social status are producing new social classes. Yet at the same time, the very processes and policies that enable these new class formations also mitigate against the development of class consciousness. Based on a year of ethnographic research in two vocational secondary schools in Nanjing, this essay looks closely at the ways in which young people who are preparing to enter the lower echelons of the urban service economy are potentially part of a new social class, but one with very limited potential to develop class consciousness.